The Stability and Influence of Barriers to Medication Adherence on Seizure Outcomes and Adherence in Children With Epilepsy Over 2 Years. (22nd June 2017) - Ramsey, Rachelle R; Zhang, Nanhua; Modi, Avani C
Abstract: Objective: To determine the stability and influence of adherence barriers on medication adherence and seizure control in pediatric epilepsy. Methods: Caregivers of 118 children aged 2–12 years old with epilepsy completed the Pediatric Epilepsy Medication Self-Management Questionnaire at nine time points over 2 years post diagnosis. Electronically monitored antiepileptic drug adherence and seizure outcome data were collected. Results: Hierarchical linear modeling results for overall barriers remained stable over 2 years. Specific item-level barriers were also generally stable over time, with the exception of running out of medication becoming more of a barrier over time. No specific barriers were related to seizure control; however, difficulties swallowing medication, forgetting, and medication refusal were related to electronically monitored adherence over time. Conclusions: Assessing for specific adherence barriers over time may lead to identification of interventions that result in improved adherence and care.